PICTORIAL COGNITIVE TASK RESOLUTION AND DYNAMICS OF EVENT-RELATED POTENTIALS - Petrek, Josef (Biomedical papers, 2008)
AIMS: To judge whether and how the character of the visual stimulus and type of cognitive task affects brain event-related potentials (ERPs).METHODS: ERPs to three types of visual stimuli (white blank oval on a dark background, unfolded cube and net of sixteen small squares) were recorded from nine scalp sites and saved on a computer. Special software was used for off-line analysis of the ERPs.RESULTS: The presentation of each of the three visual stimuli used was followed by ERPs consisting of two negative (N160, N340) and one positive (P220) components. The character of the stimulus did not affect the latency of ERPs components. However, the type of visual stimuli affected the amplitude. The most conspicuous changes were shown by the N340 ERPs component. Its average amplitude in comparison with reference amplitude was always significantly higher during the first cognitive task (``Choose the cube that can be folded up from the unfolded cube!'') and significantly lower than reference amplitude during the second cognitive task (``Complete the missing part of a figure with the appropriate item!''). It was also shown that subjective personality traits such as nervousness, spontaneous aggressivity and emotional lability had an influence on the recovery phase of the experiment affecting the average amplitude of N340 CONCLUSION: The results revealed that the cognitive processes underlying successful resolution of two pictorial cognitive tasks affected differently the activity of systems giving rise to visual ERPs.
Keywords: Cognitive task/Personality traits/ERP